The two faces of enhancing utilization of health-care services: determinants of patient initiation and retention in rural Burkina Faso - Frederick Mugisha; Kouyate Bocar; Hengjin Dong; Gloria Chepng'eno; Rainer Sauerborn (The World Health Organization, 2004)
OBJECTIVE: To explore the factors that determine whether a patient will initiate treatment within a system of health-care services, and the factors that determine whether the patient will be retained in the chosen system, in Nouna, rural Burkina Faso. METHODS: The data used were pooled from four rounds of a household survey conducted in Nouna, rural Burkina Faso. The ongoing demographic surveillance system provided a sampling framework for this survey in which 800 households were sampled using a two-stage cluster sampling procedure. More than one treatment episode was observed for a single episode of illness per patient. The multinomial logit model was used to explore the determinants of patient initiation to systems of modern, traditional and home treatment, and a binary logit model was used to explore the determinants of patient retention within the chosen health-care provider system. FINDINGS: The results suggest that the determinants of patient initiation and their subsequent retention are different. Household income, education, urban residence and expected competency of the provider are positive predictors of initiation, but not of retention, for modern health-care services. Only perceived quality of care positively predicted retention in modern health-care services. CONCLUSION: Interventions focusing on patient initiation and patient retention are likely to be different. Policies directed at enhancing initiation for modern health-care services would primarily focus on reducing financial barriers, while those directed at increasing retention would primarily focus on attributes that improve the perceived quality of care.